Carbon-coated silicon nanowire / carbon nanotube composite material as well as preparation method and application thereof

By growing carbon nanotubes in high temperature vacuum in silicon nanowires and forming carbon cladding, the high cost of silicon nanowires and oxidation problems are solved, the conductive performance and cycling capacity are improved, and efficient battery material production is achieved.

CN119208546APending Publication Date: 2024-12-27TOMI CHENGDU APPLIED TECH RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310731827.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In the prior art, the process cost of composite silicon nanowires with carbon materials is high and difficult to produce on a large scale. The surface oxidation of silicon nanowires can easily lead to a decrease in conductivity, affecting the first-effect and cycling capabilities of the battery.

Method used

By growing carbon nanotubes under medium and high temperature vacuum conditions in silicon nanowires and forming a carbon cladding layer during cooling, the conductive capacity of the silicon nanowires is increased, oxidation is avoided, and energy consumption and production costs are reduced.

Benefits of technology

The conductive performance and circulation capacity of silicon nanowires are improved, the capacity utilization rate of materials and the first cycle efficiency are enhanced, and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208546A_ABST
    Figure CN119208546A_ABST
Patent Text Reader

Abstract

The invention provides a carbon-coated silicon nanowire / carbon nanotube composite material and a preparation method and application thereof.The preparation method comprises the steps that in the cooling process of synthesizing a silicon nanowire, a first carbon source and a first catalyst are added into a vacuum environment where the silicon nanowire is located, and a carbon nanotube is generated in the silicon nanowire; and then adding a second carbon source, and reacting to form carbon coating, thereby obtaining the composite material. The carbon source gasified in vacuum and at high temperature carries the catalyst to enter the silicon nanowire for in-situ growth of the carbon nanotube, so that the contact between the carbon nanotube and the silicon nanowire is increased, and the interspersed carbon nanotube effectively increases the conductivity; carbon coating effectively inhibits expansion of the silicon nanowires after lithium intercalation, and oxidation can be effectively avoided. Residual by-products in silicon nanowire synthesis can also be removed through high-temperature vacuum treatment, and in-situ growth of carbon nanotubes and carbon coating are realized in the cooling process, so that energy consumption is effectively reduced, and cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries and relates to a negative electrode material, in particular to a carbon-coated silicon nanowire / carbon nanotube composite material and a preparation method and use thereof. Background Art

[0002] Currently, commercial lithium-ion batteries generally use graphite as the negative electrode material, but the theoretical specific capacity of graphite is only 372mAh / g, which cannot meet the needs of fields with high energy density requirements. Since silicon negative electrode material has a theoretical specific capacity of 420mAh / g and is abundant in the earth, it is considered to be one of the most promising materials.

[0003] However, silicon particles will undergo a huge volume expansion (>300%) during the lithiation process, and will shatter and fall from the current collector, which will cause the delithiation process and lead to the loss of electrical contact between particles. Silicon nanowires are a typical one-dimensional silicon nanomaterial, whose structure is conducive to axial charge transfer and makes the radial migration distance of lithium ions shorter. Silicon nanowires can effectively utilize the space between wires during the lithium insertion process to avoid the breakage and fragmentation of silicon wires caused by volume effect, which can effectively alleviate the above problems.

[0004] In the prior art, the performance of silicon nanowires is often improved by further compounding with carbon materials. However, physically and mechanically mixing silicon nanowires with carbon conductive agents in a conventional manner will result in uneven mixing, poor contact between silicon nanowires and conductive agents, and affect the capacity of silicon nanowires. In addition, silicon nanowires have high surface activity and are easily oxidized. When silicon nanowires are treated, they are easily exposed to oxygen or water to form a thick oxide layer, which seriously affects their initial efficiency and cycle capacity when used in batteries.

[0005] CN115966683A discloses a silicon-carbon microsphere negative electrode material, wherein silicon nanowires and carbon nanotubes are dispersed in a solution to obtain a silicon-carbon dispersion; the silicon-carbon dispersion is placed in a reactor for hydrothermal reaction, and then cooled and dried to obtain a silicon-carbon microsphere negative electrode material. Although the composite with graphene improves the electrical properties, the hydrothermal reaction will cause severe oxidation of the surface of the silicon nanowires, and the thicker oxide layer reduces the first effect and conductivity.

[0006] For this problem, the prior art has a technical solution to improve oxidation resistance by carbon coating:

[0007] CN110010864A discloses a silicon-graphene battery negative electrode, which uses metal cation-assisted etching of silicon wafers to obtain a silicon nanowire array, and then uses chemical vapor deposition to coat graphene on the surface of the silicon nanowire to obtain graphene-coated silicon nanowires. By coating the surface of the silicon nanowire with graphene, the conductivity of the silicon nanowire can be effectively improved, and oxidation of the silicon wire can be prevented during post-processing, but this process is costly and difficult to mass produce.

[0008] Therefore, there is still a need to develop a new technical solution to manufacture silicon nanowire and carbon composite materials in a simpler, easier and lower-cost way to achieve improved performance of silicon nanowires. Summary of the invention

[0009] In view of the problems existing in the prior art, the purpose of the present invention is to provide a carbon-coated silicon nanowire / carbon nanotube composite material and its preparation method and use. In the preparation method, during the cooling process after the synthesis of the silicon nanowire, a first carbon source and a first catalyst are added to the silicon nanowire to generate carbon nanotubes in the silicon nanowire, and then a second carbon source is added to react to form a carbon coating to obtain the composite material. In the present invention, the carbon source gasified at high temperature carries the catalyst into the silicon nanowire to grow carbon nanotubes in situ, thereby increasing the contact between the carbon nanotubes and the silicon nanowires. The interlaced carbon nanotubes effectively increase the conductivity; the carbon coating effectively inhibits the expansion of the silicon nanowire after lithium insertion, and can effectively avoid oxidation. Therefore, the use of the preparation method can effectively improve the material capacity utilization rate, improve the first cycle efficiency and cycle capacity.

[0010] To achieve this object, the present invention adopts the following technical solutions:

[0011] In a first aspect, the present invention provides a method for preparing a carbon-coated silicon nanowire / carbon nanotube composite material, comprising the following steps:

[0012] Mixing a first carbon source, a first catalyst and silicon nanowires to perform a first stage reaction to generate carbon nanotubes in the silicon nanowires;

[0013] A second carbon source is added to carry out a second stage reaction to form a carbon coating on the carbon nanotubes and the silicon nanowires to obtain a carbon-coated silicon nanowire / carbon nanotube composite material.

[0014] The first carbon source and the first catalyst are added to the silicon nanowires to generate carbon nanotubes in the silicon nanowires, and then the second carbon source is added to react to form a carbon coating to obtain the composite material. In the present invention, the carbon source gasified at high temperature carries the catalyst into the silicon nanowires to grow carbon nanotubes in situ, thereby increasing the contact between the carbon source and the silicon nanowires. The interspersed carbon nanotubes effectively increase the conductivity; the carbon coating effectively inhibits the expansion of the silicon nanowires after lithium insertion, and can effectively avoid oxidation. Therefore, the preparation method can effectively improve the material capacity utilization rate, improve the first cycle efficiency and cycle capacity. In situ growth of carbon nanotubes and carbon coating during the cooling process effectively reduces energy consumption and reduces costs.

[0015] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0016] As a preferred technical solution of the present invention, the first carbon source and the second carbon source are independently selected from any one of a liquid carbon source, a gaseous carbon source or a solid carbon source, or a combination of at least two of them. Typical but non-limiting examples of the combination include a combination of a liquid carbon source and a gaseous carbon source, a combination of a liquid carbon source and a solid carbon source, or a combination of a solid carbon source and a gaseous carbon source.

[0017] Preferably, the first carbon source is a liquid carbon source.

[0018] Preferably, the second carbon source is the same as the first carbon source.

[0019] Preferably, the liquid carbon source comprises any one of liquid paraffin, liquid glucose, benzene, acetic acid or ethyl acetate, or a combination of at least two thereof. Typical but non-limiting examples of the combination include a combination of liquid paraffin and liquid glucose, a combination of liquid paraffin and benzene, a combination of liquid paraffin and acetic acid, a combination of liquid paraffin and ethyl acetate, a combination of liquid glucose and benzene, a combination of liquid glucose and acetic acid, a combination of liquid glucose and ethyl acetate, a combination of benzene and acetic acid, a combination of benzene and ethyl acetate, or a combination of acetic acid and ethyl acetate.

[0020] Preferably, the gaseous carbon source comprises methane and / or acetylene.

[0021] Preferably, the solid carbon source comprises any one of pitch, resin or starch, or a combination of at least two of them. Typical but non-limiting examples of the combination include a combination of pitch and resin, a combination of pitch and starch, or a combination of starch and resin.

[0022] Preferably, the first catalyst comprises any one of ferrocene, nano iron powder, nickel powder or cobalt powder, or a combination of at least two thereof. Typical but non-limiting examples of the combination include a combination of ferrocene and nano iron powder, a combination of ferrocene and nickel powder, a combination of ferrocene and cobalt powder, a combination of nano iron powder and nickel powder, a combination of nano iron powder and cobalt powder, or a combination of nickel powder and cobalt powder.

[0023] As a preferred technical solution of the present invention, the first-stage reaction is carried out under a vacuum environment.

[0024] Preferably, the first carbon source and the second carbon source are liquid carbon sources, the first carbon source and the first catalyst are uniformly mixed to form a mixture, and the mixture is added to the silicon nanowires in a vacuum environment to make the gas pressure positive.

[0025] By placing the silicon nanowires in a vacuum environment in advance and then introducing a mixture containing a carbon source, the carbon nanotubes can be further promoted to enter the silicon nanowires and grow in situ in the silicon nanowires. In addition, the vacuum can effectively remove by-products in the process of generating silicon nanowires and reduce zinc chloride impurities and silicon oxide, thereby further ensuring the performance of the resulting product.

[0026] Preferably, the vacuum degree of the vacuum environment is 0.1-0.5 MPa, for example, 0.1 MPa, 0.15 MPa, 0.2 MPa, 0.25 MPa, 0.3 MPa, 0.35 MPa, 0.4 MPa, 0.45 MPa or 0.5 MPa, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0027] Preferably, when the first carbon source and the second carbon source are liquid carbon sources, the addition rates of the mixture and the second carbon source are both 1 to 5 g / min, for example, 1 g / min, 1.5 g / min, 2 g / min, 2.5 g / min, 3 g / min, 3.5 g / min, 4 g / min, 4.5 g / min or 5 g / min, etc., but are not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0028] The present invention controls the amount of carbon source added by adjusting the speed of adding the carbon source, and the carbon source is added continuously within a specified time. Intermittent addition will affect the quality of the carbon nanotubes and the coating layer.

[0029] Preferably, when the first carbon source and the second carbon source are liquid carbon sources, the mass of the first catalyst accounts for 10% to 20% of the mass of the first carbon source, for example 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0030] Preferably, when the first carbon source and the second carbon source are liquid carbon sources, the mass of the first carbon source is 1 to 2 times the mass of the silicon nanowires, for example, 1 times, 1.1 times, 1.2 times, 1.3 times, 1.4 times, 1.5 times, 1.6 times, 1.7 times, 1.8 times, 1.9 times or 2 times, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0031] Preferably, when the first carbon source and the second carbon source are liquid carbon sources, the mass of the second carbon source is 3 to 5 times the mass of the silicon nanowires, for example, 3 times, 3.1 times, 3.2 times, 3.3 times, 3.4 times, 3.5 times, 3.6 times, 3.7 times, 3.8 times, 3.9 times, 4 times, 4.1 times, 4.2 times, 4.3 times, 4.4 times, 4.5 times, 4.6 times, 4.7 times, 4.8 times, 4.9 or 5 times, etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0032] As a preferred technical solution of the present invention, both the first-stage reaction and the second-stage reaction are continuous cooling processes.

[0033] Preferably, the cooling rates of the first stage reaction and the second stage reaction are independently selected from 1 to 5°C / min, for example, 1g / min, 1.5g / min, 2g / min, 2.5g / min, 3g / min, 3.5g / min, 4g / min, 4.5g / min or 5g / min, but are not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0034] Preferably, the starting temperature of the first stage reaction is 700-1000°C, for example, 700°C, 730°C, 760°C, 790°C, 820°C, 850°C, 880°C, 910°C, 940°C, 970°C or 1000°C, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0035] Preferably, the reaction time of the first stage is 30 to 60 min, for example, 30 min, 33 min, 36 min, 39 min, 42 min, 45 min, 48 min, 51 min, 54 min, 57 min or 60 min, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0036] Preferably, the reaction time of the second stage is 30 to 60 min, for example, 30 min, 33 min, 36 min, 39 min, 42 min, 45 min, 48 min, 51 min, 54 min, 57 min or 60 min, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0037] Preferably, after the second stage reaction is completed, the mixture is naturally cooled to room temperature, and then impurities are washed with dilute hydrochloric acid and deionized water, and the carbon-coated silicon nanowire / carbon nanotube composite material is obtained after drying.

[0038] As a preferred technical solution of the present invention, the silicon nanowires are prepared according to the following method, which includes: heating a silicon source, a second catalyst and a reducing agent to react to obtain silicon nanowires.

[0039] The present invention can synthesize silicon nanowires by CVD, and complete the growth of carbon nanowire tubes, i.e., carbon coating, in the silicon nanowires during the cooling stage after the synthesis of the silicon nanowires. Specifically, after the synthesis of the silicon nanowires, the high temperature is maintained and the vacuum is drawn, which can remove the reaction byproducts in the silicon nanowires, such as zinc chloride, and on the other hand, put the silicon nanowires in a vacuum environment, and then the temperature is lowered and the carbon source is introduced. Under the conditions of vacuum and high temperature, the carbon source is helped to enter and disperse inside the silicon nanowires, greatly improving the distribution uniformity of the carbon nanotubes and their contact area and bonding force with the silicon nanowires, effectively improving the conductivity of the silicon nanowires, and the in-situ growth of the carbon nanotubes and the carbon coating completed during the cooling process also reduces energy consumption and reduces costs.

[0040] Preferably, the silicon source comprises silicon tetrachloride.

[0041] Preferably, the second catalyst comprises metal powder or metal chloride powder of any one or at least two of Au, Ag, Cu, Pt, Ni, Co or Ti, such as metal powder or metal chloride powder of Au and Ag, metal powder or metal chloride powder of Au and Cu, metal powder or metal chloride powder of Au and Pt, metal powder or metal chloride powder of Au and Ni, metal powder or metal chloride powder of Au and Co, metal powder or metal chloride powder of Au and Ti, metal powder or metal chloride powder of Ag and Cu, metal powder or metal chloride powder of Ag and Pt, metal powder or metal chloride powder of Ag and Ni, metal powder or metal chloride powder of Ag and Co, metal powder or metal chloride powder of Ag and Ti, metal powder or metal chloride powder of Cu and Pt, metal powder or metal chloride powder of Cu and Ni, metal powder or metal chloride powder of Cu and Co, or metal powder or metal chloride powder of Cu and Ti.

[0042] Preferably, the particle size of the second catalyst is less than 50 μm, for example 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 49 μm, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0043] Preferably, the reducing agent includes metal powders of any one or at least two of Mg, Al, Zn or Fe, such as metal powders of Mg and Al, metal powders of Mg and Zn, metal powders of Mg and Fe, metal powders of Al and Zn, metal powders of Al and Fe, metal powders of Zn and Fe, etc.

[0044] Preferably, the particle size of the reducing agent is less than 500 μm, for example 5 μm, 10 μm, 30 μm, 50 μm, 80 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm or 490 μm, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0045] Preferably, the mass of the second catalyst is 1% to 5% of the mass of the reducing agent, for example 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0046] Preferably, the ratio of the molar amount of the silicon source to the molar amount of the reducing agent is 1:(1-2), for example 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9 or 1:2, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0047] As a preferred technical solution of the present invention, the heating reaction is carried out under a flowing protective atmosphere.

[0048] Preferably, the protective atmosphere comprises argon.

[0049] Preferably, the temperature of the heating reaction is 700-1000°C, for example 700°C, 730°C, 760°C, 790°C, 820°C, 850°C, 880°C, 910°C, 940°C, 970°C or 1000°C, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0050] Preferably, the heating reaction time is 30 to 60 min, for example 30 min, 33 min, 36 min, 39 min, 42 min, 45 min, 48 min, 51 min, 54 min, 57 min or 60 min, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0051] Preferably, after the heating reaction is completed, the flow of the protective atmosphere is stopped, and the temperature is kept for 10 to 30 minutes, such as 10 minutes, 12 minutes, 14 minutes, 16 minutes, 18 minutes, 20 minutes, 22 minutes, 24 minutes, 26 minutes, 28 minutes or 30 minutes, etc., but it is not limited to the listed values, and other values ​​not listed in the above numerical range are also applicable. At the same time, vacuum is drawn to remove residual chloride, and vacuum is stopped after the insulation is completed, so that the obtained silicon nanowires are in a vacuum environment.

[0052] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0053] (1) placing a reducing agent and a second catalyst in a tubular furnace, controlling the mass of the second catalyst to be 1% to 5% of the mass of the reducing agent, using argon to replace oxygen in the tube, maintaining the argon gas flow to heat up to 700 to 1000° C., introducing a silicon source, controlling the molar ratio of the silicon source to the molar ratio of the reducing agent to be 1:(1 to 2), performing a heating reaction for 30 to 60 minutes, generating silicon nanowires, stopping the introduction of argon after the heating reaction, continuing to keep the temperature for 10 to 30 minutes and evacuating, maintaining the vacuum degree at 0.1 to 0.5 MPa, and removing chlorides in the silicon nanowires;

[0054] (2) placing a liquid carbon source and a first catalyst into a container and stirring to form a mixture; after the insulation in step (1) is completed, the vacuum is stopped and the temperature is lowered at 1 to 5°C / min, while the stirring in the container is maintained. A peristaltic pump is used to pump the mixture into the high temperature zone of the tubular furnace at a feeding rate of 1 to 5 g / min, so that the air pressure is positive, and the tail gas valve is opened to exhaust the gas, and the first stage reaction is carried out for 30 to 60 minutes to generate carbon nanotubes; the stirring in the container is stopped to allow the first catalyst to settle, and only the liquid carbon source in the container is pumped into the high temperature zone of the tubular furnace at a feeding rate of 1 to 5 g / min, and the second stage reaction is carried out for 30 to 60 minutes to form a carbon coating on the carbon nanotubes and the silicon nanowires; after naturally cooling to room temperature, impurities are cleaned with dilute hydrochloric acid and deionized water, and the carbon-coated silicon nanowire / carbon nanotube composite material is obtained after drying.

[0055] In a second aspect, the present invention provides a carbon-coated silicon nanowire / carbon nanotube composite material, wherein the composite material is obtained using the preparation method described in the first aspect.

[0056] Preferably, in the carbon-coated silicon nanowire / carbon nanotube composite material, the mass of the carbon nanotubes is 5% to 20% of the mass of the silicon nanowires, for example 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0057] Preferably, in the carbon-coated silicon nanowire / carbon nanotube composite material, the mass of the carbon coating layer is 50% to 200% of the mass of the silicon nanowire, for example, 50%, 60%, 70%, 80%, 90%, 100%, 110%, 120%, 130%, 140%, 150%, 160%, 170%, 180%, 190% or 200%, etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0058] In a second aspect, the present invention provides a negative electrode material, wherein the negative electrode material contains the carbon-coated silicon nanowire / carbon nanotube composite material described in the second aspect.

[0059] In a third aspect, the present invention provides an ion battery, wherein the ion battery contains the negative electrode material described in the second aspect.

[0060] Compared with the prior art solutions, the present invention has at least the following beneficial effects:

[0061] After the synthesis of silicon nanowires is completed, the present invention removes byproducts adsorbed on the silicon nanowires, such as zinc chloride, through high-temperature vacuum, thereby increasing the penetration of carbon sources in the silicon nanowires. In the subsequent cooling process, the energy during the cooling is used to grow carbon nanotubes and form a carbon coating layer, thereby reducing energy consumption. The conductivity of the silicon nanowires is increased by directly synthesizing carbon nanotubes in the silicon nanowires, thereby avoiding the problem of poor mixing and poor contact between the material and the conductive agent when the conductive agent is directly added. The carbon source is carbonized and then deposited on the surface of the silicon nanowire to form a coating layer, thereby isolating the silicon nanowire from contact with oxygen and effectively preventing the silicon nanowire from being oxidized in subsequent treatments. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1 is a scanning electron microscope image of the silicon nanowire / carbon nanotube composite material obtained in Example 1;

[0063] Figure 2 is a scanning electron microscope image of the carbon-coated silicon nanowire / carbon nanotube composite material obtained in Example 1;

[0064] Figure 3 The cycle test diagram of the button batteries obtained in Example 1, Comparative Example 1 and Comparative Example 2;

[0065] Figure 4 This is a cycle test diagram of the button battery obtained in the control group. DETAILED DESCRIPTION

[0066] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0067] Example 1

[0068] This embodiment provides a carbon-coated silicon nanowire / carbon nanotube composite material and a preparation method thereof, the preparation method comprising the following steps:

[0069] (1) placing 100 g of reducing agent zinc powder and 1 g of second catalyst copper powder in a tube furnace, controlling the mass of the second catalyst to be 1 / 1 of the mass of the reducing agent, using argon to replace oxygen in the tube, maintaining the argon gas flow and heating to 800° C., introducing 200 g of silicon source, controlling the molar ratio of the silicon source to the molar ratio of the reducing agent to be 1:1.52, and performing heating reaction for 50 min to generate silicon nanowires. After the heating reaction is completed, stopping the introduction of argon, continuing to keep the temperature for 10 min and evacuating to 0.5 MPa to remove chlorides in the silicon nanowires;

[0070] (2) 220 g of liquid carbon source liquid paraffin and 22 g of the first catalyst ferrocene are placed in a container and stirred to form a mixture. After the insulation in step (1) is completed, the vacuum is stopped and the temperature is lowered at 3°C / min. The stirring in the container is maintained, and the mixture is pumped into the high temperature zone of the tubular furnace using a peristaltic pump at a feeding rate of 2 g / min. When the air pressure is positive, the tail gas valve is opened to exhaust the gas, and the exhaust is continued to be supplied, and the first stage reaction is carried out for 30 minutes to generate carbon nanotubes to obtain a silicon nanowire / carbon nanotube composite material; the stirring in the container is stopped to allow the first catalyst to settle, and only the liquid carbon source in the container is pumped into the high temperature zone of the tubular furnace at a feeding rate of 2 g / min to carry out a second stage reaction for 30 minutes to form a carbon coating on the carbon nanotubes and the silicon nanowires. After naturally cooling to room temperature, impurities are cleaned with dilute hydrochloric acid and deionized water, and the carbon-coated silicon nanowire / carbon nanotube composite material is obtained after drying.

[0071] Example 2

[0072] This embodiment provides a carbon-coated silicon nanowire / carbon nanotube composite material and a preparation method thereof, the preparation method comprising the following steps:

[0073] (1) placing 100 g of zinc powder as a reducing agent and 1 g of copper powder as a second catalyst in a tube furnace, controlling the mass of the second catalyst to be 1 / 1 of the mass of the reducing agent, replacing oxygen in the tube with argon gas, maintaining the temperature of the argon gas flow to 700° C., introducing 160 g of a silicon source, controlling the molar ratio of the silicon source to the molar ratio of the reducing agent to be 1:1.9, and performing a heating reaction for 60 min to generate silicon nanowires. After the heating reaction is completed, stopping the introduction of argon gas, continuing to keep the temperature for 10 min and evacuating to 0.5 MPa to remove chlorides in the silicon nanowires;

[0074] (2) 200 g of liquid carbon source liquid paraffin and 40 g of the first catalyst ferrocene are placed in a container and stirred to form a mixture. After the insulation in step (1) is completed, the vacuum is stopped and the temperature is lowered at 2°C / min. The stirring in the container is maintained, and the mixture is pumped into the high temperature zone of the tubular furnace using a peristaltic pump at a feed rate of 1 g / min. When the air pressure is positive, the tail gas valve is opened to exhaust the gas, and the first stage reaction is carried out for 60 minutes to generate carbon nanotubes; the stirring in the container is stopped to allow the first catalyst to settle, and only the liquid carbon source in the container is pumped into the high temperature zone of the tubular furnace at a feed rate of 1 g / min. The second stage reaction is carried out for 60 minutes to form a carbon coating on the carbon nanotubes and the silicon nanowires. After naturally cooling to room temperature, impurities are cleaned with dilute hydrochloric acid and deionized water, and the carbon-coated silicon nanowire / carbon nanotube composite material is obtained after drying.

[0075] Example 3

[0076] This embodiment provides a carbon-coated silicon nanowire / carbon nanotube composite material and a preparation method thereof, the preparation method comprising the following steps:

[0077] (1) placing 100 g of reducing agent zinc powder and 1 g of second catalyst copper powder in a tube furnace, controlling the mass of the second catalyst to be 1 / 1 of the mass of the reducing agent, using argon to replace oxygen in the tube, maintaining the argon gas flow and heating to 900° C., introducing 240 g of a silicon source, controlling the molar ratio of the silicon source to the molar ratio of the reducing agent to be 1:1.26, and performing a heating reaction for 40 min to generate silicon nanowires. After the heating reaction is completed, stopping the introduction of argon, continuing to keep the temperature for 10 min and evacuating to 0.5 MPa to remove chlorides in the silicon nanowires;

[0078] (2) 400 g of liquid carbon source liquid paraffin and 40 g of the first catalyst ferrocene are placed in a container and stirred to form a mixture. After the insulation in step (1) is completed, the vacuum is stopped and the temperature is lowered at 4°C / min. The stirring in the container is maintained, and the mixture is pumped into the high temperature zone of the tubular furnace using a peristaltic pump at a feed rate of 4 g / min. When the air pressure is positive, the tail gas valve is opened to exhaust the gas, and the first stage reaction is carried out for 50 minutes to generate carbon nanotubes; the stirring in the container is stopped to allow the first catalyst to settle, and only the liquid carbon source in the container is pumped into the high temperature zone of the tubular furnace at a feed rate of 4 g / min, and the second stage reaction is carried out for 50 minutes to form a carbon coating on the carbon nanotubes and the silicon nanowires. After naturally cooling to room temperature, impurities are cleaned with dilute hydrochloric acid and deionized water, and the carbon-coated silicon nanowire / carbon nanotube composite material is obtained after drying.

[0079] Example 4

[0080] This embodiment provides a carbon-coated silicon nanowire / carbon nanotube composite material and a preparation method thereof, the preparation method comprising the following steps:

[0081] (1) placing 100 g of zinc powder as a reducing agent and 1 g of copper powder as a second catalyst in a tube furnace, controlling the mass of the second catalyst to be 1 / 1 of the mass of the reducing agent, replacing oxygen in the tube with argon gas, maintaining the temperature at 1000° C., introducing 260 g of a silicon source, controlling the molar ratio of the silicon source to the molar ratio of the reducing agent to be 1:1.17, and performing a heating reaction for 30 min to generate silicon nanowires. After the heating reaction is completed, stopping the introduction of argon gas, continuing to keep the temperature for 10 min and evacuating to 0.5 MPa to remove chlorides in the silicon nanowires;

[0082] (2) 400 g of liquid carbon source liquid paraffin and 60 g of the first catalyst ferrocene are placed in a container and stirred to form a mixture. After the insulation in step (1) is completed, the vacuum is stopped and the temperature is lowered at 5°C / min. The stirring in the container is maintained, and the mixture is pumped into the high temperature zone of the tubular furnace using a peristaltic pump at a feed rate of 5 g / min. When the air pressure is positive, the tail gas valve is opened to exhaust the gas, and the first stage reaction is carried out for 40 minutes to generate carbon nanotubes; the stirring in the container is stopped to allow the first catalyst to settle, and only the liquid carbon source in the container is pumped into the high temperature zone of the tubular furnace at a feed rate of 5 g / min. The second stage reaction is carried out for 40 minutes to form a carbon coating on the carbon nanotubes and the silicon nanowires. After naturally cooling to room temperature, impurities are cleaned with dilute hydrochloric acid and deionized water, and the carbon-coated silicon nanowire / carbon nanotube composite material is obtained after drying.

[0083] Example 5

[0084] This embodiment provides a carbon-coated silicon nanowire / carbon nanotube composite material and a preparation method thereof. The preparation method is identical to that of Embodiment 1 except that in step (2), the feed rate of the mixture is adjusted from 2 g / min to 1 g / min.

[0085] Example 6

[0086] This embodiment provides a carbon-coated silicon nanowire / carbon nanotube composite material and a preparation method thereof. The preparation method is identical to that of Embodiment 1 except that in step (2), the feed rate of the mixture is adjusted from 2 g / min to 3 g / min.

[0087] Example 7

[0088] This embodiment provides a carbon-coated silicon nanowire / carbon nanotube composite material and a preparation method thereof. The preparation method is exactly the same as that of Example 1 except that in step (2), the feed rate of the mixture is adjusted from 2 g / min to 4 g / min.

[0089] Example 8

[0090] This embodiment provides a carbon-coated silicon nanowire / carbon nanotube composite material and a preparation method thereof. The preparation method is exactly the same as that of Example 1 except that in step (2), the feed rate of the mixture is adjusted from 2 g / min to 5 g / min.

[0091] Example 9

[0092] The present embodiment provides a carbon-coated silicon nanowire / carbon nanotube composite material and a preparation method thereof. The preparation method is identical to that of Example 1 except that in step (2), stirring in the container is stopped to allow the first catalyst to settle, and only the feed rate of the liquid carbon source in the container is adjusted from 2 g / min to 1 g / min and pumped into the high temperature zone of the tubular furnace.

[0093] Example 10

[0094] The present embodiment provides a carbon-coated silicon nanowire / carbon nanotube composite material and a preparation method thereof. The preparation method is identical to that of Example 1 except that in step (2), stirring in the container is stopped to allow the first catalyst to settle, and only the feed rate of the liquid carbon source in the container is adjusted from 2 g / min to 3 g / min and the liquid carbon source is pumped into the high temperature zone of the tubular furnace.

[0095] Embodiment 11

[0096] The present embodiment provides a carbon-coated silicon nanowire / carbon nanotube composite material and a preparation method thereof. The preparation method is identical to that of Example 1 except that in step (2), stirring in the container is stopped to allow the first catalyst to settle, and only the feed rate of the liquid carbon source in the container is adjusted from 2 g / min to 4 g / min and pumped into the high temperature zone of the tubular furnace.

[0097] Example 12

[0098] The present embodiment provides a carbon-coated silicon nanowire / carbon nanotube composite material and a preparation method thereof. The preparation method is identical to that of Example 1 except that in step (2), stirring in the container is stopped to allow the first catalyst to settle, and only the feed rate of the liquid carbon source in the container is adjusted from 2 g / min to 5 g / min and pumped into the high temperature zone of the tubular furnace.

[0099] Example 13

[0100] The present embodiment provides a carbon-coated silicon nanowire / carbon nanotube composite material and a preparation method thereof. The preparation method is identical to the first embodiment except that in step (2), the cooling rate is adjusted from 3°C / min to 0°C / min, i.e., no cooling is performed and the temperature is maintained unchanged.

[0101] Embodiment 14

[0102] The present embodiment provides a carbon-coated silicon nanowire / carbon nanotube composite material and a preparation method thereof. The preparation method is identical to the first embodiment except that in step (2), the cooling rate is adjusted from 3°C / min to 2°C / min, i.e., no cooling is performed and the temperature is maintained unchanged.

[0103] Embodiment 15

[0104] The present embodiment provides a carbon-coated silicon nanowire / carbon nanotube composite material and a preparation method thereof. The preparation method is identical to the first embodiment except that in step (2), the cooling rate is adjusted from 3°C / min to 5°C / min, i.e., no cooling is performed and the temperature is maintained unchanged.

[0105] Example 16

[0106] The present embodiment provides a carbon-coated silicon nanowire / carbon nanotube composite material and a preparation method thereof. The preparation method is identical to the first embodiment except that in step (2), the cooling rate is adjusted from 3°C / min to 7°C / min, i.e., no cooling is performed and the temperature is maintained unchanged.

[0107] Embodiment 17

[0108] This embodiment provides a composite material and a preparation method thereof. The difference between the preparation method and embodiment 1 is that the vacuum treatment is not performed in step (1). That is, the preparation method of this embodiment includes the following steps:

[0109] (1) placing 100 g of reducing agent zinc powder and 1 g of second catalyst copper powder in a tube furnace, controlling the mass of the second catalyst to be 1 / 1 of the mass of the reducing agent, using argon gas to replace oxygen in the tube, maintaining the argon gas flow and heating to 800° C., introducing 200 g of silicon source, controlling the molar ratio of the silicon source to the molar ratio of the reducing agent to be 1:1.52, and performing heating reaction for 50 min to generate silicon nanowires. After the heating reaction is completed, stopping the introduction of argon gas and continuing to keep warm for 10 min;

[0110] (2) 220 g of liquid carbon source liquid paraffin and 22 g of the first catalyst ferrocene are placed in a container and stirred to form a mixture. After the insulation in step (1) is completed, the temperature is lowered at 3°C / min, and the stirring in the container is maintained. The mixture is pumped into the high temperature zone of the tubular furnace using a peristaltic pump at a feed rate of 2 g / min, and the tail gas valve is opened to exhaust. The mixture is continued to be fed, and the first stage reaction is carried out for 30 minutes to generate carbon nanotubes; the stirring in the container is stopped to allow the first catalyst to settle, and only the liquid carbon source in the container is pumped into the high temperature zone of the tubular furnace at a feed rate of 2 g / min, and the second stage reaction is carried out for 30 minutes to form a carbon coating on the carbon nanotubes and the silicon nanowires. After naturally cooling to room temperature, impurities are cleaned with dilute hydrochloric acid and deionized water, and the carbon-coated silicon nanowire / carbon nanotube composite material is obtained after drying.

[0111] Comparative Example 1

[0112] This comparative example provides a composite material and a preparation method thereof. The difference between the preparation method and Example 1 is that carbon coating is not performed in step (2). That is, step (2) of the preparation method in this comparative example is:

[0113] 220 g of liquid carbon source liquid paraffin and 22 g of the first catalyst ferrocene are placed in a container and stirred to form a mixture. After the insulation in step (1) is completed, the vacuum is stopped and the temperature is lowered at 3°C / min. The stirring in the container is maintained and the mixture is pumped into the high temperature zone of the tubular furnace using a peristaltic pump at a feeding rate of 2 g / min. When the gas pressure is positive, the tail gas valve is opened to exhaust gas and the gas is continued to be fed. The first stage reaction is carried out for 30 minutes to generate carbon nanotubes. After naturally cooling to room temperature, impurities are washed with dilute hydrochloric acid and deionized water, and the composite material is obtained after drying.

[0114] Except for the above, other conditions are exactly the same as those in Example 1.

[0115] Comparative Example 2

[0116] This comparative example provides a composite material and a preparation method thereof. The difference between the preparation method and Example 1 is that carbon nanotubes are not generated in step (2). That is, step (2) of the preparation method in this comparative example is:

[0117] 220 g of liquid carbon source liquid paraffin is placed in a container and stirred. After the insulation in step (1) is completed, the vacuum is stopped and the temperature is lowered at 3°C / min. The stirring in the container is maintained and the liquid paraffin is pumped into the high temperature zone of the tubular furnace using a peristaltic pump at a feed rate of 2 g / min. When the gas pressure is positive, the tail gas valve is opened to exhaust gas and the exhaust is continued. The first stage reaction is carried out for 30 minutes. After naturally cooling to room temperature, impurities are cleaned with dilute hydrochloric acid and deionized water and dried to obtain a carbon-coated silicon nanowire / carbon nanotube composite material.

[0118] Except for the above, other conditions are exactly the same as those in Example 1.

[0119] Control group

[0120] This control group used the silicon nanowires obtained in step (1) of Example 1 for subsequent testing.

[0121] The composite materials obtained in the embodiment and the comparative example and the silicon nanowires in the control group were respectively mixed with a certain amount of graphite to form negative electrode materials, and button batteries were made according to the mass ratio of negative electrode material to binder of 9:1. The batteries were cycled for 100 times at 0.5C, and the results are recorded in Table 1.

[0122] Table 1

[0123]

[0124]

[0125] Combination Figure 1-4 From Table 1, we can see that:

[0126] (1) Figure 1 and Figure 2 The scanning electron microscope images of the silicon nanowire / carbon nanotube composite material and the carbon-coated silicon nanowire / carbon nanotube composite material obtained in Example 1 respectively show that carbon nanotubes are grown interspersed in the middle of the silicon nanowires, and a large number of carbon nanotubes are also grown on their surfaces; after carbon coating, a dense coating layer is formed on the surfaces of the silicon nanowires and carbon nanotubes.

[0127] In Example 2, due to the low growth temperature at the initial stage, the grown carbon nanotubes are shorter, the carbon deposited on the surface is less, and the uncoated silicon nanowires are more, which affects the conductivity; in Example 3 and Example 4, the initial reaction temperature is higher than that in Example 1, and the carbon layer subsequently deposited on the surface of the nanowires and carbon nanotubes is slightly thicker, which affects the lithium insertion and removal ability of the material;

[0128] (2) Figure 3 and Figure 4 It can be seen that compared with Example 1, in Comparative Example 1, carbon nanotubes are not coated after growth, and the expansion of silicon nanowires cannot be effectively alleviated, but the carbon nanotubes are in good contact with the silicon nanowires, and the first efficiency is higher than that of the pure silicon nanowires in Comparative Example 2 and the control group; in Comparative Example 2, a carbon layer is directly deposited on the surface of the silicon nanowire to form a coating layer. Since no carbon nanotubes are formed, the material itself has poor conductivity and a low first efficiency. The formed carbon layer effectively alleviates the expansion of the silicon nanowires, and the capacity retention rate after 100 cycles is greater than that of Comparative Example 1; the silicon nanowires in the control group are directly mixed with graphite, the surface of the silicon nanowires is greatly oxidized, and the exposed silicon nanowires consume too much lithium, resulting in a low first efficiency. The silicon nanowires are directly in contact with the electrolyte, and SEI films are repeatedly formed during the charge and discharge process, and the capacity decrease after the cycle is relatively large;

[0129] (3) By comparing Example 1 with Example 17, it is found that the residual zinc chloride in the silicon nanowires will seriously reduce the first efficiency and cycle performance.

[0130] (4) By comparing Example 1 with Examples 5-8, it is found that: when the amount of carbon nanotubes generated increases, the gram capacity of the negative electrode material decreases, the first efficiency increases, and the cycle performance improves. More carbon nanotubes help to improve the conductive properties of the negative electrode material.

[0131] (5) By comparing Example 1 with Examples 9-12, it is found that: when the thickness of the coating layer increases, the specific capacity of the negative electrode material decreases, the first efficiency decreases, and the cycle performance decreases. A thicker carbon layer is not conducive to the conduction of lithium ions, and more amorphous carbon will also reduce the cycle capacity.

[0132] (6) By comparing Example 1 with Examples 13-16, it was found that temperature affects the growth quality and effect of carbon nanotubes, and also affects the thickness and quality of the carbon-coated carbon layer. When the cooling rate increases, the growth quality of the carbon nanotubes deteriorates and the thickness of the carbon layer becomes thinner, resulting in a decrease in the coating rate, which affects the initial effect and cycle capacity of the negative electrode material.

[0133] As can be seen from the above, after the synthesis of silicon nanowires is completed, the present invention removes the zinc chloride adsorbed on the silicon nanowires through high-temperature vacuum; in the cooling process, the energy during the cooling is used to grow carbon nanotubes and form a carbon coating layer, thereby reducing energy consumption; the conductivity of the silicon nanowires is increased by synthesizing carbon nanotubes in the silicon nanowires, thereby avoiding the problem of poor mixing and poor contact between the material and the conductive agent when the conductive agent is directly added; and the carbon source is carbonized and deposited on the surface of the silicon nanowire to form a coating layer, thereby isolating the silicon nanowire from contact with oxygen and preventing the silicon nanowire from oxidation in subsequent treatments.

[0134] The present invention illustrates the detailed structural features of the present invention through the above embodiments, but the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0135] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0136] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0137] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing a carbon-coated silicon nanowire / carbon nanotube composite material, characterized in that: The steps include: Mixing a first carbon source, a first catalyst and silicon nanowires to perform a first-stage reaction to generate carbon nanotubes in the silicon nanowires; A second carbon source is added to carry out a second stage reaction to form a carbon coating on the carbon nanotubes and the silicon nanowires to obtain a carbon-coated silicon nanowire / carbon nanotube composite material.

2. The preparation method according to claim 1, characterized in that: The first carbon source and the second carbon source are independently selected from any one or a combination of at least two of a liquid carbon source, a gaseous carbon source or a solid carbon source; Preferably, the first carbon source is a liquid carbon source; Preferably, the second carbon source is the same as the first carbon source; Preferably, the liquid carbon source comprises any one or a combination of at least two of liquid paraffin, liquid glucose, benzene, acetic acid or ethyl acetate; Preferably, the gaseous carbon source comprises methane and / or acetylene; Preferably, the solid carbon source comprises any one of asphalt, resin or starch, or a combination of at least two thereof; Preferably, the first catalyst comprises any one of ferrocene, nano iron powder, nickel powder or cobalt powder, or a combination of at least two thereof.

3. The preparation method according to claim 1 or 2, characterized in that: The first stage reaction is carried out under vacuum; Preferably, the first carbon source and the second carbon source are liquid carbon sources, the first carbon source and the first catalyst are uniformly mixed to form a mixture, and the mixture is added to the silicon nanowires in a vacuum environment to make the gas pressure positive; Preferably, the vacuum degree of the vacuum environment is 0.1-0.5 MPa; Preferably, when the first carbon source and the second carbon source are liquid carbon sources, the addition rates of the mixture and the second carbon source are both 1-5 g / min; Preferably, when the first carbon source and the second carbon source are liquid carbon sources, the mass of the first catalyst accounts for 10% to 20% of the mass of the first carbon source; Preferably, when the first carbon source and the second carbon source are liquid carbon sources, the mass of the first carbon source is 1 to 2 times the mass of the silicon nanowires; Preferably, when the first carbon source and the second carbon source are liquid carbon sources, the mass of the second carbon source is 3 to 5 times the mass of the silicon nanowires.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The first stage reaction and the second stage reaction are both continuous cooling processes; Preferably, the cooling rates of the first stage reaction and the second stage reaction are independently selected from 1 to 5°C / min; Preferably, the starting temperature of the first stage reaction is 700-1000°C; Preferably, the first stage reaction time is 30 to 60 minutes; Preferably, the second stage reaction time is 30 to 60 minutes; Preferably, after the second stage reaction is completed, the mixture is naturally cooled to room temperature, and then impurities are washed with dilute hydrochloric acid and deionized water, and the carbon-coated silicon nanowire / carbon nanotube composite material is obtained after drying.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The silicon nanowires are prepared according to the following method, which includes: heating a silicon source, a second catalyst and a reducing agent to react to obtain silicon nanowires; Preferably, the silicon source comprises silicon tetrachloride; Preferably, the second catalyst comprises metal powder or metal chloride powder of any one or at least two of Au, Ag, Cu, Pt, Ni, Co or Ti; Preferably, the particle size of the second catalyst is less than 50 μm; Preferably, the reducing agent comprises metal powder of any one or at least two of Mg, Al, Zn or Fe; Preferably, the particle size of the reducing agent is less than 500 μm; Preferably, the mass of the second catalyst is 1% to 5% of the mass of the reducing agent; Preferably, the molar ratio of the silicon source to the reducing agent is 1:(1-2).

6. The preparation method according to claim 5, characterized in that: The heating reaction is carried out under a flowing protective atmosphere; Preferably, the protective atmosphere comprises argon; Preferably, the temperature of the heating reaction is 700-1000°C; Preferably, the heating reaction time is 30 to 60 minutes; Preferably, after the heating reaction is completed, the flow of the protective atmosphere is stopped, the temperature is kept for 10 to 30 minutes and vacuum is drawn to remove residual chlorides. After the temperature is kept, vacuum drawing is stopped to place the obtained silicon nanowires in a vacuum environment.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) placing a reducing agent and a second catalyst in a tubular furnace, controlling the mass of the second catalyst to be 1% to 5% of the mass of the reducing agent, using argon to replace oxygen in the tube, maintaining the argon gas flow to heat up to 700 to 1000° C., introducing a silicon source, controlling the molar ratio of the silicon source to the molar ratio of the reducing agent to be 1:(1 to 2), performing a heating reaction for 30 to 60 minutes, generating silicon nanowires, stopping the introduction of argon after the heating reaction, continuing to keep the temperature for 10 to 30 minutes and evacuating, maintaining the vacuum degree at 0.1 to 0.5 MPa, and removing chlorides in the silicon nanowires; (2) placing a liquid carbon source and a first catalyst into a container and stirring to form a mixture; after the insulation in step (1) is completed, the vacuum is stopped and the temperature is lowered at 1 to 5°C / min, while the stirring in the container is maintained. A peristaltic pump is used to pump the mixture into the high temperature zone of the tubular furnace at a feeding rate of 1 to 5 g / min, so that the air pressure is positive, and the tail gas valve is opened to exhaust the gas, and the first stage reaction is carried out for 30 to 60 minutes to generate carbon nanotubes; the stirring in the container is stopped to allow the first catalyst to settle, and only the liquid carbon source in the container is pumped into the high temperature zone of the tubular furnace at a feeding rate of 1 to 5 g / min, and the second stage reaction is carried out for 30 to 60 minutes to form a carbon coating on the carbon nanotubes and the silicon nanowires; after naturally cooling to room temperature, impurities are cleaned with dilute hydrochloric acid and deionized water, and the carbon-coated silicon nanowire / carbon nanotube composite material is obtained after drying.

8. A carbon-coated silicon nanowire / carbon nanotube composite material, characterized in that: Obtained by the preparation method according to any one of claims 1 to 7; Preferably, in the carbon-coated silicon nanowire / carbon nanotube composite material, the mass of the carbon nanotube is 5% to 20% of the mass of the silicon nanowire; Preferably, in the carbon-coated silicon nanowire / carbon nanotube composite material, the mass of the carbon coating layer is 50% to 200% of the mass of the silicon nanowire.

9. A negative electrode material, characterized in that: A carbon-coated silicon nanowire / carbon nanotube composite material comprising the carbon-coated silicon nanowire / carbon nanotube composite material according to claim 8.

10. An ion battery, characterized in that: Contains the negative electrode material according to claim 9.